Circulation of heterogeneous Carnivore protoparvovirus 1 in diarrheal cats and prevalence of an A91S feline panleukopenia virus variant in China. Issue 5 (9th July 2022) - Chen, Xi; Wang, Jiali; Zhou, Yuxing; Yue, Hua; Zhou, Ning; Tang, Cheng
Abstract: Cats are susceptible to panleukopenia virus (FPV) and canine parvovirus type 2 (CPV‐2) infection. FPV has been recognized as relatively conservative in genetic evolution compared to CPV‐2, but information regarding FPV variations in cats is still limited. The aim of this study was to investigate the molecular prevalence of FPV and CPV‐2 variants among cats in China. From April 2019 to December 2021, 193 diarrheal faecal samples of cats were collected from Southwest China and 127 (65.80%) samples tested positive to Carnivore protoparvovirus 1 . FPV, CPV‐2 and some their genomic variants were identified from positive samples, indicating a heterogeneous Carnivore protoparvovirus 1 circulation in the cat population in China. Among FPV strains, an A91S FPV mutant reached the detection rate of 39.37%, which showed that this FPV genomic variant has been prevalent in the tested cats. Moreover, 7 strains of A91S FPV variants were isolated and purified successfully using F81 cells, and the genomes were sequenced. Phylogenetic trees based on the nearly complete genomic sequences, VP2 and NS1 nucleotide sequences showed that the A91S FPV variants were located in the FPV clade, but all clustered into a separate branch. Structural prediction showed that A91S mutation in VP2 protein extended the random coil of aa residues from 92–95 to 91–95. Moreover, the analysis of all complete VP2 sequences of FPV and CPV‐2 available in the GenBank database revealed that the A91S FPV variant has been prevalent in China since 2017 and has reported in four other countries in cats. Thus, our study revealed that heterogeneous Carnivore protoparvovirus 1 are circulating in the cat population in China, and first reported the prevalence and genomic characteristics of the A91S FPV variant, which contributed to a better understanding of the molecular prevalence and genetic evolution of FPV in cats.